FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TUBERKULOSIS PARU PADA TENAGA KERJA DI KECAMATAN SUKMAJAYA, KOTA DEPOK TAHUN 2023 - Abdullah Hamdan Wafi (2023)
Pulmonary Tuberculosis is an infectious disease caused by mycobacterium tuberculosis with symptoms of shortness of breath accompanied by a chronic cough. Sukmajaya District is the area with the highest pulmonary TB cases in Depok City. This study aims to determine the factors associated with the incidence of pulmonary TB in workers in Sukmajaya District, Depok City in 2023. This research is a quantitative study using a case-control study design. The population in this study amounted to 832 people. A sample of 128 respondents, consisting of 64 cases and 64 controls, was obtained using a purposive sampling technique. Data were analyzed using the Chi-square test. The results of the analysis showed that the factors associated with the incidence of pulmonary TB in the workforce included gender (p-value=0.001; OR=3.78), ventilation (p-value=0.000; OR=11.05), smoking habits (p-value=0.000; OR=10.02), and contact history (p-value=0.000; OR=24.16), while there is no relationship between education level (p-value=0.365), type of work (p-value = 0.479) and knowledge (p-value = 0.051) with the incidence of pulmonary TB in the workforce. Efforts to prevent transmission of pulmonary TB are needed in the workforce with screening programs carried out in government and private agencies in collaboration with the puskesmas.